Kinetics and mechanisms of leaching of rare earth elements from secondary resources. (February 2022) - Ait Brahim, Jamal; Ait Hak, Sara; Achiou, Brahim; Boulif, Rachid; Beniazza, Redouane; Benhida, Rachid
Graphical abstract: Highlights: Description of the mechanisms controlling REEs leaching in secondary resources. Comparison of kinetics models in the leaching of REEs from secondary resources. Suggestion of kinetics approaches for optimizing the leaching of REEs. Classification of secondary resources of REEs in terms of economic opportunities. Abstract: The study of the kinetics of REEs from secondary resources and the understanding of the mechanisms governing the leaching reactions are fundamental aspects for the design and the optimization of industrial processes. Despite their interest, the kinetic aspect of these valuable elements from secondary resources has not been reviewed yet. Therefore, a deep understanding of the major phenomena involved in the elementary stages of REEs leaching is extremely crucial and would allow setting up a comprehensive methodology for kinetics investigation. This review provides a state of the art on various kinetics approaches describing the leaching kinetics and mechanisms of REEs from secondary resources notably low-grade minerals, industrial residues as well as end-of-life products. Different existing kinetics models applied for the leaching were reviewed and deeply discussed. Meanwhile, comparative study of different leaching mechanisms was also realized for a better understanding of the REEs leaching reactions. More importantly, the effect of different leaching parameters on the kinetics was discussed for further optimization and development of REEs extraction processes from secondary resources. In addition, the comparison of different REEs secondary resources was provided in terms of content, availability and economic opportunities to target the most potentially and economically viable resources.